Identification of direct reporting of individual taxpayers to the tax service office using the Ishikawa diagram - Dharmakarja, I Gede Made Artha; Kusuma, I Gede Komang Chahya Bayu Anta; Andriana, Nina (Educoretax, 2025)
Filing the Individual Taxpayer’s Annual Tax Return (WPOP SPT) is designed to be a straightforward process that can be completed independently using an application. However, many taxpayers face difficulties in calculating, filling out, and submitting their Individual Taxpayer Annual Tax Return for Personal Income Tax (SPT PPh OP), leading to a high volume of in-person visit queues to Tax Offices (KPP). This study aims to identify the root causes of these challenges and their impact on tax administration, particularly the increasing service demands and long queues at tax offices. The research was conducted through observations and interviews with taxpayers (WP) at the Pondok Aren Tax Office. A fishbone (Ishikawa) diagram was used to analyze the causes of these issues, while a literature review applied the MECE (Mutually Exclusive, Collectively Exhaustive) method and the 5M framework (Man, Materials, Machines, Methods, Money), supplemented by considerations of information and time factors. The findings indicate that the primary issue lies in the human factor (Man), specifically, taxpayers’ limited knowledge and understanding of tax procedures. Other technical factors are difficulties in operating the application (Machines) and the completeness of report preparation support (Materials). Prior research frequently recommends that tax officers improve taxpayers’ education and promote the use of digital tax reporting platforms. Tax officers remain essential in providing education and support. Additionally, tax volunteers can play a crucial role in assisting taxpayers, particularly during peak reporting periods. To improve service quality, tax officers should receive training in customer service excellence, while tax offices must enhance computer infrastructure and internet capacity to prevent system disruptions.